CHALLENGES IN IMPLEMENTING TAXES ON E-COMMERCE TRANSACTIONS IN MALAYSIA - MOHD RIZAL PALIL; HOD BIN AMIN; SITI ZAIDAH TURMIN (Jurnal Bisnis dan Akuntansi, 2020)
Electronic commercial transactions are growing rapidly, thereby causing unease among conventional traders who believe that the taxation system is unfair to them because of loopholes that cause e-commerce traders to avoid taxes. The government’s perspective is that e-traders cause losses in taxes that could otherwise increase the country’s revenue and harmonize the tax system among all traders, whether e-commerce or conventional. Various views have been expressed on the implications of e-commerce; some argue that e-commerce improves the tax system, whereas others believe that the tax system was designed prior to the emergence of e-commerce, thereby creating problems in Malaysia. Therefore, this study investigates the problems posed by e-commerce, especially in identifying challenges in taxation. Based on systematic literature highlights, 6 major challenges have been identified, consisting of 22 items in tax implementation for e-commerce in Malaysia. A quantitative research approach has been used to ensure generalization of opinions on tax implementation challenges that are appropriate to the context of taxation in the country. Based on the feedback received by 73 respondents consisting of officers involved in the Malaysian tax system, the reflective–formative hierarchical model was analyzed using a structural equation model through SmartPLS software to address the tax implementation challenges for e-commerce. This study is regarded as beneficial for the parties involved, especially the Inland Revenue Board, in designing efficient and systematic tax rules and guidelines on e-commerce so that potential tax sources can be identified and losses can be reduced.